1997
DOI: 10.1002/(sici)1096-9101(1997)21:1<20::aid-lsm4>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Development of a smart Holmium:YAG laser lithotriptor

Abstract: Background and Objective: The purpose of this study was to develop a feedback control system for the pulsed holmium: YAG medical laser that enhances tissue selectivity and safety by discriminating between soft and hard biological tissue such as urinary and biliary calculi and bone. Study Design/Materials and Methods: The ability to discriminate is achieved by monitoring prompt laser-induced visible/ NIR photoemissions via retrograde transmission over the laser delivery fiber in conjunction with a developed det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Goldey et al . in 1997 reported the development of a smart Holmium:YAG laser lithotripter which discriminated stone and tissue by monitoring laser‐induced visible/NIR photoemission . Contrary to those results, we could not measure a strong luminescence signal in vitro at the beginning of a laser pulse regularly, but quite irregularly on stone as well as on tissue.…”
Section: Introductioncontrasting
confidence: 62%
“…Goldey et al . in 1997 reported the development of a smart Holmium:YAG laser lithotripter which discriminated stone and tissue by monitoring laser‐induced visible/NIR photoemission . Contrary to those results, we could not measure a strong luminescence signal in vitro at the beginning of a laser pulse regularly, but quite irregularly on stone as well as on tissue.…”
Section: Introductioncontrasting
confidence: 62%
“…For Ho:YAG laser‐induced incandescence, according to Goldey at al. the signal emitted by calculi is thermally induced radiation emitted from the calculus surface . They used this signal for stone/tissue discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, Goldey et al reported the development of a “smart” Ho:YAG laser lithotriptor . They were able to discriminate soft and hard biological tissue by monitoring prompt laser‐induced visible/NIR photoemissions via retrograde transmission over the laser delivery fiber in in vitro studies and an animal experiment.…”
Section: Introductionmentioning
confidence: 99%
“…This automatic feedback prevented the laser being triggered when the fiber was incorrectly positioned on tissue. Goldey et al reported a similar development for the Ho:YAG laser lithotripter, but no clinical data have been published to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 97%